Ecotoxicity of Malathion® 500 CE before and after UVC radiation and UV/H2O2 treatment - Adams, Eliane; de Paula, Vinicius de Carvalho Soares; Carneiro, Rhaissa Dayane; de Lima, Rubia Matos; Gomes, Monike Felipe; Ramsdorf, Wanessa Algarte; Martins de Freitas, Adriane (Eclética Química, 2018)
Since 2008, Brazil has been the largest consumer of agrochemicals in the world, using pesticides to combat pests and vectors, impacting both microbiota and human health. Aiming at the degradation of the contaminants present in the environment, treatments by advanced oxidative processes are based on the synthesis of free radicals that allow the degradation of the pollutant. Among these processes are included UV/H2O2. By evaluating the ecotoxicity and phytotoxicity of the commercial Malathion® 500 CE product, using Aedes aegypti larvae and Lactuca sativa seed, the high toxicity of this formulation was observed. EC50 values for A. aegypti being equal to 0.4 μg L-1 and for L. sativa equal to 550 μg L-1. The commercial agrochemical degradation was carried out by UVC radiation and UV/H2O2, and the toxicity was evaluated after 30 and 120 minutes. After both treatments, the percentage of immobility was zero for A. aegypti, inferring the efficiency of the processes. However, for L. sativa, no treatment was able to remove or reduce initial toxicity.